FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI MASYARAKAT TERHADAP VAKSIN COVID-19 - FELLYA ALMA HESTI; Wan Nishfa Dewi; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Vaccination is one of the government's programs to cope with COVID-19 in Indonesia. Public perception of the COVID-19 vaccine is a response of a new issue in Indonesia related to vaccines. Differences perception of the COVID-19 vaccine are influenced by several perception-forming factors that will affect the success of this vaccination program. This study aims to determine contributing factors toward public perceptions of COVID-19 Vaccine. This study used a descriptive correlation design with a cross sectional approach. The research sample amounted to 100 people who were taken based on the inclusion criteria using cluster sampling technique. The analysis used is bivariate analysis using chi-square test. The results of the statistical test showed that out of 100 respondents 60 people (60%) had a positive perception and 40 respondents (40%) had a negative perception of the COVID-19 vaccine. Variables related to public perception of the COVID-19 vaccine were experience of exposure to COVID-19 (p=0.037), experience of vaccination (p=0.018) and knowledge of vaccination (p=0.000). While the variables that did not have a relationship were age (p=0.582), gender (p=0.342), education level (p=0.786) and ethnicity (p=0.201). The experience of being exposed to COVID-19, vaccination experience and Knowledge have a relationship with people's perceptions of the COVID-19 vaccine. It is recommended to provide comprehensive and evenly distributed information to all the public with the latest information about COVID-19 vaccination.Keywords: COVID-19, Perception, Public, Vaccine